Self-Organized Three-Dimensional Nanostructured Architectures in Bulk GaN Generated by Spatial Modulation of Doping. (18th February 2016) - Tiginyanu, Ion; Stevens-Kalceff, Marion A.; Sarua, Andrei; Braniste, Tudor; Monaico, Eduard; Popa, Veaceslav; Andrade, Hugo D.; Thomas, James O.; Raevschi, Simion; Schulte, Karl; Adelung, Rainer
Abstract : Self-organized 3D nanostructured architectures including quasi-ordered concentric hexagonal structures generated during the growth of single crystalline n -GaN substrates by hydride vapor phase epitaxy (HVPE) are reported. The study of as-grown samples by using Kelvin Probe Force Microscopy shows that the formation of self-organized architectures can be attributed to fine modulation of doping related to the spatial distribution of impurities. The specific features of nanostructured architectures involved have been brought to light by using electrochemical and photoelectrochemical etching techniques which are highly sensitive to local doping. The analysis of the results shows that the formation of self-organized spatial architectures in the process of HVPE is caused by the generation of V-pits and their subsequent overgrowth accompanied by the growth in variable direction. It is demonstrated for the first time that the electrical and luminescence properties of HVPE-grown GaN are spatially modulated throughout, including islands between overgrown V-pit regions. The dependence of doping upon growth direction is confirmed by the micro-cathodoluminescence characterization of HVPE-grown pencil-like microcrystals exposing various crystallographic planes along the tip. These results are indicative of new possibilities for defect engineering in gallium nitride and for three-dimensional spatial nanostructuring of this important electronic material by controlling the growth direction.